KNOWLEDGE ON INFECTION PREVENTION AND CONTROL AMONG STUDENTS IN UNIVERSITAS PADJADJARAN DENTAL HOSPITAL - Paham, Aulia Narendra Mohamad; Malinda, Yuti; Setiawan, Ame Suciati (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Dentist is one of the professions that are vulnerable to the transmission of infectious diseases there is hence it requires proper infection control. The educational hospital is responsible for carrying out infection control training that includes appropriate standard precautions for dental students before carrying out educational activities in the hospital so that students are ready to treat patients. This study aims to determine the knowledge of interns and residents at Universitas Padjadjaran Dental Hospital on infection prevention and control.Method: This is a quantitative descriptive study with a cross-sectional approach using data from the training section of Universitas Padjadjaran Dental Hospital from August 2020 to February 2021. Determination of the number of samples taken using the Isaac and Michael formula and using a proportionate stratified random sampling technique.Result: The average value of interns and residents are the same, which is 71, seen also from the average percentage of those who answered correctly on the questionnaire which showed similar results between interns and residents. Conclusion: Knowledge on infection prevention and control among interns and residents are the same, with knowledge classified in the sufficient category.